THE IMPORTANCE OF PRIORITIZING REQUESTS IN SERVICING PROCESS - Zakirov, V.M.; Abdullaev, E.S. (SCIENCE and SOCIETY, 2024)
This article also examines the benefits of offering support based on the importance of remote teams’ demands for service time. Additionally, the impact of the order of requests on the time it takes to supply services was explored.